The burden of diarrhoeal diseases in the Democratic Republic of Congo: a time-series analysis of the global burden of disease study estimates (1990-2019) - Gloire O. Mbaka; Rute Vieira (BMC, 2022)
Abstract Background Diarrhoeal diseases are important causes of disability and mortality being one of the main causes of mortality in the Democratic Republic of Congo (DRC). One of the largest and wealthiest African countries, DRC has been for long subjected to continuous political and economic instability, conflicts and disease outbreaks. This study aimed to address the knowledge gap in understanding how prevalence, mortality and burden of diseases in DRC changed over time and examine the influence of specific factors in these disease-related outcomes. Methods A time-series analysis of the Global Burden of Diseases, Injuries, and Risk Factors Study 2019 estimates was performed to describe prevalence, years lived with disabilities (YLDs) and mortality due to diarrhoeal diseases, by age-group and sex, between 1990-2019 in DRC. The contribution of water, sanitation and hygiene (WASH) and child malnutrition risk factors to these outcomes was also analysed. Piecewise regression analysis was used to assess trends over time. Results The overall age-standardised prevalence of diarrhoeal diseases for both sexes in DRC was 1350.84 (UI:1240.16-1461.62) cases per 100,000 people in 1990. The prevalence increased until 2019, also fuelled by the movement of Rwandan refugees to DRC and First/Second Congo wars between 1996-2003. Age-standardised prevalence and mortality were consistently higher in males, compared to females, decreasing by 42% and 54%, respectively, between 1990 and 2019. Overall prevalence was also usually higher in over 70 years old, except between 1998-2003 when mortality in under five years old was the highest. Unsafe water sources and child wasting among under five years old were the main contributors to YLDs and deaths associated to diarrhoeal diseases in DRC. Conclusion Diarrhoeal diseases are important and preventable causes of disability and mortality in DRC. National measures of surveillance and cost-effective interventions targeting the identified risk groups could be effective in reducing its prevalence and associated burden.